Sericite Ore Prospects in Huong Son - Ky Anh region (Ha Tinh Province) - Xuân, Phạm Tích; Phổ, Nguyễn Văn; Trà, Đoàn Thu; Nga, Hoàng Tuyết; Đăng, Phạm Thanh; Liên, Nguyễn Thị; Thảo, Nguyễn Thị Thanh (Vietnam Journal of Earth Sciences, 2014)
Huong Son and Ky Anh districts are located in Ha Tinh province where are two sericite mineralization areas discovered, in Son Binh (Huong Son district) and Ky Tay (Ky Anh district). One of them, the sericite resource of Son Binh deposit, is hypothetically estimated about 2,79 million tons. Hydrothermal alterations, mostly sericitization of rhyolites and rhyolite tuffs are causes of formation of sericite in Middle Triassic Dong Trau formation (Lower Sub - formation). The most prospective sericite mineral regions in Huong Son - Ky Anh are Son Binh deposit and south Cam Xuyen - Ky Anh area.